The Implementation Of E-Learning To Overcome Learning Loss In Covid-19 Post-Pandemic In Islamic Education At Al-Ma’arif Junior High Jombang-Jember - Sahlan, Moh.; Mursalim, Mursalim; Umam, Khotibul; Subakri, Subakri (CV. Inara, 2022)
The current state of the COVID-19 pandemic, which has entered the New Normal Era, has harmed education in the form of learning loss. This research examines of e-learning implementation to deal with learning loss in Islamic Education (PAI) subjects at al Ma’arif Junior High in Jombang Jember. This research applies a qualitative approach with study case type and analyzes data through the interactive technique of Miles, Huberman, and Saldana. This research concludes some states that e-learning implementation at al Ma’arif Junior High in Jombang Jember to deal with learning loss focuses on two things. First, upgrading the learning technology of al Ma’arif Junior High in Jombang Jember is centered on maximizing school web role. Second, increasing students learning motivation to follow the e-learning process that implemented by al Ma’arif Junior High in Jombang Jember. The Efforts to implement e-learning can be considered as one of the solution options that can be carried out by educational institutions to deal with the phenomenon of learning loss during the New Normal Era.